2016
DOI: 10.2214/ajr.15.15367
|View full text |Cite
|
Sign up to set email alerts
|

Automated Breast Ultrasound in Breast Cancer Screening of Women With Dense Breasts: Reader Study of Mammography-Negative and Mammography-Positive Cancers

Abstract: Combining mammography with ABUS, compared with mammography alone, significantly improved readers' detection of breast cancers in women with dense breast tissue without substantially affecting specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(45 citation statements)
references
References 26 publications
4
40
0
1
Order By: Relevance
“…Kelly et al [20] reported an increase in sensitivity from 40% for mammography alone to 81% with the addition of ABUS. In a recent study comparing FFDM with 3D ABUS to FFDM alone for mammography-negative cancers, the addition of 3D ABUS caused a 23.9% sensitivity increase [21]. The small loss of specificity in our study (−0.7%) compares favorably to the −13.4% specificity loss reported in the Somoinsight study [11].…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Kelly et al [20] reported an increase in sensitivity from 40% for mammography alone to 81% with the addition of ABUS. In a recent study comparing FFDM with 3D ABUS to FFDM alone for mammography-negative cancers, the addition of 3D ABUS caused a 23.9% sensitivity increase [21]. The small loss of specificity in our study (−0.7%) compares favorably to the −13.4% specificity loss reported in the Somoinsight study [11].…”
Section: Discussionsupporting
confidence: 45%
“…The setup of our study was similar to the Somoinsight study by Brem et al [11] and the reader performance studies by Skaane et al [30] and GIGER et al [21]. In all three studies the first reader assessed the mammogram and then 3D ABUS.…”
Section: Discussionmentioning
confidence: 94%
“…Our results are in agreement with the similar results showing an increase of the sensitivity of cancer detection by 36% using ABUS in combination with mammography reported by Wilczek et al [13] and Kelly et al [14]. The previous findings are also in agreement with Giger et al [15] who stated a statistically significant increase in the detection rate of cancers with the use of ABUS combined with FFDM in patients with extremely dense breasts. Brem et al [16] stated an increased rate of cancer detection with the addition of ABUS to screening mammography in patients with dense breasts; however, there was an increase in the number of false positive results as well.…”
Section: Discussionsupporting
confidence: 94%
“…In a multireader, multicase reader study, 17 radiologists interpreted the images from 185 examinations of FFDM alone and FFDM with ABUS, with results showing ABUS+FFDM significantly improved readers' breast cancer detection. [22] Sensitivity was shown to increase significantly in cases of mammography negative cancers, by 23.9%. Specificity was shown to be similar as well; 78.1% for FFDM and 76.1% for FFDM+ABUS, the difference in which did not reach statistical significance.…”
Section: Utilization Of Screening Us Post-legislationmentioning
confidence: 94%